Будова статевої системи молюсків підродини Physinae - Гарлінська, Алла; Garlinska, Alla (Східноєвропейський національний університет імені Лесі Українки, 2015)
Здійснено аналіз кількісних показників статевої системи семи видів молюсків підродини Physinae (Physa fontinalis, Ph. adversa, Ph. skinneri, Ph. bulla, Physella acuta, Phys. heterostropha, Costatella integra) із застосуван- ням сучасних методів багатовимірної статистики. З’ясовано, що кількісні ознаки статевої системи можуть бути використані для ідентифікації видів. The analysis of morphometric parameters of Physinae subfamily species and the analysis of allozymic variability as well prove this subfamily to be represented with three species – Physa fontinalis, Ph. skinneri, Physella acuta in the fauna of Ukraine. But their reliable identification based only on conchiological signs is rather a problem. The use of some anatomical signs is more reliable. Thus, Ph. skinneri is well differentiated from others with the length of copulative apparatus, the length of the penis bag and their correlation; Ph. fontinalis and Phys. acuta are reliably differentiated with spermatheca and oviduct parameters.
The Structure of Physinae Subfamily Mollusc Reproductive System.
Keywords: Physinae; статева система; багатовимірна статистика; копулятивний апарат; Physinae; reproductive system; multivariate statistics; copulative apparatus